Embryogenesis and organogenesis of Mexican creole avocado - Quintero-Jiménez, Anareli; Heredia-García, Elena; Aguirre-Mancilla, César Leobardo; Raya-Pérez, Juan Carlos; Ramírez-Pimentel, Juan Gabriel; Iturriaga, Gabriel (Revista Mexicana de Ciencias Agrícolas, 2020)
The Drymifolia avocado variety (Persea americana Mill.) is generally used as rootstock, so it is important to implement somatic embryogenesis and in vitro organogenesis techniques for its genetic improvement, conservation and clonal propagation. In this work, direct and indirect somatic embryogenesis and organogenesis of the Drymifolia variety were evaluated. Germination of the mature somatic embryos was induced with 0.5 mg L-1 of 6-N-benzyl amino purine (BAP) and 1 mg L-1 of gibberellic acid (GA3). Of the six accessions evaluated, Celaya 79, Comonfort 53, San Miguel, BG24, BG181 and Zutano, only San Miguel responded to the embryogenesis process. In direct embryogenesis, the highest regeneration efficiency was obtained with 0.2 mg L-1 of picloram (46%) and 10 mg L-1 of ANA (40%). In indirect embryogenesis, the San Miguel accession formed callus with 0.2 mg L-1 of picloram and had a regeneration efficiency of 45%, conserving its regeneration potential for up to six months. Regarding organogenesis, decapitated immature zygotic embryos were cultured in medium with or without growth regulators and all six accessions responded positively to both conditions. The Comonfort 53 accession had higher regeneration efficiency (54%) with growth regulators. This study carried out from 2016 to 2018, provides a new and promising approach for the regeneration and multiplication of P. americana var. Drymifolia through zygotic embryos.
Keywords: avocado; Drymifolia; in vitro regeneration; micropropagation